1999
DOI: 10.1108/03684929910282962
|View full text |Cite
|
Sign up to set email alerts
|

Neural transmission‐errors, cerebral arousability and hemisphericity

Abstract: Suggests that the arousability theory of intelligence and personality of Robinson (1996) lacks two important factors: the influence of neural transmission errors and of hemisphericity on intelligence and personality. It is considered that at least two factors contribute to intelligence. The first factor is the potential energetic level of Hebb’s engrams, which may be related to arousability. The second factor is the probability of neural transmission errors. It is suggested that the theory of H.J. Eysenck, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Its purpose is to characterize some fundamental neurological factors which underly several, if not all, of the cognitive functions. We have suggested in previous studies (Fidelman, 1998a; 1999a) two such factors.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Its purpose is to characterize some fundamental neurological factors which underly several, if not all, of the cognitive functions. We have suggested in previous studies (Fidelman, 1998a; 1999a) two such factors.…”
Section: Introductionmentioning
confidence: 83%
“…Another factor suggested in the earlier studies (Fidelman, 1998a; 1999a) is the probability of neural transmission errors at individual synapses. If the quantity of available transmitter is too large, there may be an increase in the post synaptic dendritic potential even if the presynaptic neuron did not fire (for example, due to remains of the transmitter).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our theory of psychometric intelligence is that high IQ is related to a small probability of transmission errors in the central neural system (Hendrickson and Hendrickson, 1982;Eysenck and Eysenck, 1985;Fidelman, 1999Fidelman, , 2001. The Hendricksons found a positive correlation between high IQ and low probability of neural transmission errors.…”
Section: Psychometric Iqmentioning
confidence: 96%
“…Studies have confirmed that subjects with higher IQ level demonstrate higher probability of error-less transmissions due to the well-functioning excitatory and inhibitory neurotransmitters. The low constant probability of transmission errors result in smaller deviation of rhythmic EEG [9] and are reflected in higher alpha power [10]. Concurrently, intelligent individuals exhibit low cerebral arousability due to inhibition of brainstem to external excitations.…”
Section: Introductionmentioning
confidence: 99%